2004
DOI: 10.1016/j.jasms.2004.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and data analysis techniques for lipid and phospholipid chemistry elucidation by intact cell MALDI-FTMS

Abstract: Ions attributed to lipids and phospholipids are directly observed by desorption from whole bacteria using intact cell (IC) matrix-assisted laser desorption-ionization (MALDI) Fourier transform mass spectrometry (FTMS). Saccharomyces cerevisiae are grown in rich media broth, concentrated, and applied directly to the MALDI surface without lysis or chemical treatment. FTMS of MALDI ions gives excellent signal to noise ratios with typical resolving powers of 90,000 and mass precision better than 0.002 Da. Use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 43 publications
(52 reference statements)
2
72
0
Order By: Relevance
“…33 MALDI-TOF MS has also been applied to obtain abundant, accurate mass ion signals of the phospholipids in bacteria. [34][35][36][37][38][39] Therefore, the characterization of lipids in bacteria and other microorganisms plays a crucial role for taxonomic identification, differentiation of pathogenic species, and understanding of metabolic processes under normal or stressed growth conditions. However, there are few reports on the application of online MALDI-TOF MS coupling with lipid profiling for identification of bacterial species.…”
Section: Introductionmentioning
confidence: 99%
“…33 MALDI-TOF MS has also been applied to obtain abundant, accurate mass ion signals of the phospholipids in bacteria. [34][35][36][37][38][39] Therefore, the characterization of lipids in bacteria and other microorganisms plays a crucial role for taxonomic identification, differentiation of pathogenic species, and understanding of metabolic processes under normal or stressed growth conditions. However, there are few reports on the application of online MALDI-TOF MS coupling with lipid profiling for identification of bacterial species.…”
Section: Introductionmentioning
confidence: 99%
“…4,[10][11][12][13][14][15][16][17] Even with the disadvantage of relatively low sensitivity, the direct-infusion ESI-FTMS approach is very easy to implement and also provides a good method to compare the global lipid distributions of two total lipid extracts under inspection.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] FTMS can provide a mass resolution on the order of 90,000 below m/z 1,000 and allow a mass accuracy of 10 ppm or better in a broad band analysis. 4 These advantages become even more powerful in the analysis of small molecular species such as lipids that generally have relatively low mass values and exist within a narrow mass range, particularly, m/z 400-1,000. [5][6][7][8] Indeed, a number of groups have shown that FTMS is a very effective tool in lipid analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MALDI have been applied to analyze lipid extracts or lipids in whole cell bacteria [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%